Do the Necessary to Clamp the Short-term Indwelling Urinary Catheter before Removal among Inpatients? A Meta-analysis of Randomized Controlled Trials (Bangladesh Journal of Medical Science, 2026)
Background Indwelling Urinary Catheter is frequently used for multiple tasks. It may lead to complications for patients. Moreover, there were no established instructions in clinical practice regarding the use of bladder clamping. Notably, each medical professional decides whether to clamp the catheter prior to removal based on their individual judgment of its necessity. Objective Identifying necessary to clamp the short-term indwelling urinary catheter before removal among inpatients. Materials and Methods Following PRISMA guidelines. Searches were conducted in the following electronic databases to identify relevant studies: the CINAHL, the Cochrane Library, Embase, Ovid-Medline, PubMed, Scopus, and Web of Science from their inception until February 5, 2023. We manually searched for relevant articles by reviewing the reference lists of included articles. Two authors performed the search independently. Data was analyzed using Comprehensive Meta-Analysis 2.0 and quality assessment was done using ROB 2.0. Continuous variables were analyzed using mean difference and standardized mean difference (SMD) values with a 95% CI. Categorical variables were analyzed using relative risk (RR) and 95% CI. Results Eight randomized controlled trials met our inclusion criteria. The Clamping IUC group highly increased the risk of urinary tract infection and needed for re-catheterization, had longer time to first voiding, and produced a smaller first voiding volume compared to the free draining group. Conclusions The results from this meta-analysis demonstrated no necessary clamped IUC before removal.BJMS, Vol. 25 No. 01 January’26 Page : 269-280